Soil warming increased whole-tree water use of Pinus cembra at the treeline in the Central Tyrolean Alps - Wieser, Gerhard (Tree Physiol, 2015)
The study quantified the effect of soil warming on sap flow density (Q(s)) of Pinus cembra at treeline in the Central Tyrolean Alps. To enhance soil temperature we installed a transparent roof construction above the forest floor around six trees. Six other trees served as controls in the absence of any manipulation. Roofing enhanced growing season mean soil temperature by 1.6, 1.3, and 1.0 °C at 5, 10, and 20 cm soil depth, respectively, while soil water availability was not affected. Sap flow density (using Granier-type thermal dissipation probes) and environmental parameters were monitored throughout three growing seasons. During the first year of treatment, no warming effect was detected on Q(s). However, soil warming caused Q(s) to increase significantly by 11 and 19% above levels in control trees during the second and third year, respectively. This effect appeared to result from warming-induced root production, a reduction in viscosity and perhaps an increase also in root hydraulic conductivity. Hardly affected were leaf-level net CO(2) uptake rate and conductance for water vapor, so that water-use efficiency stayed unchanged as confirmed by needle δ(13)C analysis. We conclude that tree water loss will increase with soil warming, which may alter the water balance within the treeline ecotone of the Central Austrian Alps in a future warming environment.